A chip-integrated coherent photonic-phononic memory - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (Nature Communications, 2017)
Controlling and manipulating quanta of coherent acoustic vibrations - phonons - in integrated circuits has recently drawn a lot of attention, since phonons can function as unique links between radiofrequency and optical signals, allow access to quantum regimes and offer advanced signal processing capabilities. Recent approaches based on optomechanical resonators have achieved impressive quality factors allowing for storage of optical signals. However, so far these techniques have been limited in bandwidth and are incompatible with multi-wavelength operation. In this work, we experimentally demonstrate a coherent buffer in an integrated planar optical waveguide by transferring the optical information coherently to an acoustic hypersound wave. Optical information is extracted using the reverse process. These hypersound phonons have similar wavelengths as the optical photons but travel at five orders of magnitude lower velocity. We demonstrate the storage of phase and amplitude of optical information with gigahertz bandwidth and show operation at separate wavelengths with negligible cross-talk.
CRIS-Team Scopus Importer:2021-06-29